The Incidence Rate and Risk Factors of Malignancy in Elderly-Onset Inflammatory Bowel Disease: A Chinese Cohort Study From 1998 to 2020 - Wang, Zheng; Zhang, Huimin; Yang, Hong; Zhang, Mengmeng; Qian, Jiaming (Frontiers in Oncology, 2021)
Background: Patients suffering inflammatory bowel disease (IBD) have an increased risk of cancer. However, the risk of malignancy in patients with elderly-onset IBD (≥60 years) remains controversial. Hence, we aimed to identify and compare the dissimilarities in morbidity and related risk factors between patients with elderly-onset and adult-onset (18-59 years) IBD in a Chinese cohort. Methods: Patients with confirmed IBD, diagnosed at age ≥18 years, between January 1998 and December 2020 at the Peking Union Medical College Hospital were enrolled. The yearly incidence rates (IRs) for cancer were calculated, and the characteristics were analyzed in these patients. Results: A total of 1480 patients suffering adult-onset IBD and 129 patients suffering elderly-onset IBD with a median follow-up period of 4.9 years and 4.8 years, respectively, were included. Patients in the elderly-onset IBD group demonstrated an increased overall incidence of cancer than that demonstrated by patients in the adult-onset group (IR 26.9 versus 9.51, respectively, per 1000 person-years; relative risk [RR], 2.83). Colorectal cancer was the most common malignancy in the two groups, and patients suffering elderly-onset IBD demonstrated a higher incidence of the malignancy (IR, 7.07 versus 3.34, respectively, per 1000 person-years; RR, 2.12). Among the extraintestinal cancers, hematological malignancies and urinary tract cancers (including renal and urinary bladder carcinoma) were common in the elderly-onset group (IR, 4.24 and 4.24 per 1000 person-years, respectively), whereas thyroid cancer was more common in the adult-onset group (IR, 1.36 per 1000 person-years). Analysis of clinical characteristics revealed that patients with elderly-onset IBD who developed cancer were more likely to have diabetes and urinary lithiasis (p=0.041 and 0.035, respectively). In addition, patients in the elderly-onset group had a shorter course from IBD to cancer, less exposure to immunosuppressants, less extraintestinal manifestations, and higher cancer-related mortality. Cox proportional risk regression analysis in the elderly-onset IBD group revealed that diabetes was an independent risk factor for the progression to cancer (hazard ratio [HR], 5.67; p=0.038). Conclusion: The risk of malignancy in patients suffering elderly-onset IBD increased significantly as compared with those with adult-onset disease. Therefore, cancer monitoring should be initiated earlier for patients in the elderly-onset group.